GRAFTING OF GROWING POLYMERIC CHAINS - Khan, A Rasheed; Ahmed, Khalil; Ifrahim, A F K (Biological Sciences - PJSIR, 2001)
Growing polymerchainsofvinylacetateweregraftedontocaseininanaqueousmediumat60°Cusing K1S20X asinitiator. The effectsofmonomerconcentration,backboneconcentrationandactivatorconcentrationweredetermined.Grafting was confirmed by elemental analysis, solubility,IR spectroscopy and intrinsic viscosity.